Increase of Efficiency of Public Administration in the Conditions of Dynamic Development of Russia - Valery Pavlovich Gridnev (Управленческое консультирование)
Article is devoted to actual problems of improvement of activity of public authorities, increases of their efficiency in modern conditions. In it the main content of activity of federal government bodies and need of increase of efficiency of functioning of the system of public administration directed on the solution of actual tasks, in particular, on creation of standard and legal base, improvement of the state personnel policy, including introduction of system of mentoring, increase of a role of modern administrative and organizational culture of the XXI century in public authorities reveals. In article proposals of the author on increase of system effectiveness of public administration in the conditions of global challenges and threats to security of mankind in the XXI century are presented and proved.